The impacts of nutrient supply and imbalance on subcontinental co‐occurrence networks and metacommunity composition of stream algae. Issue 7 (11th May 2021) - Budnick, William R.; Mruzek, Joseph L.; Larson, Chad A.; Passy, Sophia I.
Abstract : The amounts and ratios of nutrients (nitrogen and phosphorus) are important determinants of producer community biodiversity and composition and their responses to climate and dispersal. However, the nutrient effects on co‐occurrence network topology, particularly in freshwaters, are understudied. Here, we investigate 1) whether nutrient supply and ratio constrain topological properties of algal co‐occurrence networks in streams and 2) to what extent climate and space (a surrogate for dispersal) affect co‐occurrence network topology versus metacommunity composition across nutrient supply and ratio contexts. We used a subcontinental dataset of benthic algae from 840 stream localities in the conterminous US. We constructed co‐occurrence networks representing nutrient supply contexts (oligotrophic versus eutrophic) and nutrient ratio contexts (N‐limited versus P‐limited) and statistically assessed topological variability within each pair via randomization. We then used a null model framework and direct gradient analysis to ascertain the importance of climate and space in driving, respectively, network topology and metacommunity composition. Nutrient supply was only positively related to network size (species node counts), which was driven by motile species, while other topological differences were non‐significant. Climatic and spatial variables had pronounced and for the most part comparable effects on network topology that further depended on nutrient context. A comparative assessment of topological versus compositional responses to climate and space across nutrient contexts identified both similarities and differences. While climate and space contributed to both network topology and metacommunity composition, space was a stronger predictor of compositional variability than climate, regardless of nutrient context. Our findings highlight the need for developing integrative multi‐level approaches (from metacommunities to co‐occurrence networks) to fully understand biological responses to complex and interactive abiotic forces.